Apophasis as the common root of radically secular and radically orthodox theologies - Franke, William (International journal for philosophy of religion, 2013)
On the one hand, we find secularized approaches to theology stemming from the Death of God movement of the 1960s, particularly as pursued by North American religious thinkers such as Thomas J.J. Altizer, Mark C. Taylor, Charles Winquist, Carl Raschke, Robert Scharlemann, and others, who stress that the possibilities for theological discourse are fundamentally altered by the new conditions of our contemporary world. Our world today, in their view, is constituted wholly on a plane of immanence, to such an extent that traditional appeals to faith in an other world become difficult to take as more than self-deception and willful blindness to our human reality. On the other hand, we hear the assertion of a new lease on life for theology and its traditional affirmation of divine transcendence over and against the putative arrogance of all claims of human autonomy. This claim is advanced particularly by theologians grouped under the banner of the so-called Radical Orthodoxy. Emanating from England, originally from the University of Cambridge in the 1980s and 1990s, this movement includes such theological thinkers as John Milbank, Graham Ward, Rowan Williams, and Catherine Pickstock. It has also explicitly styled itself “post-secularist.” I propose that both approaches are based on not very fully acknowledged and often explicitly denied premises in negative theology, which surprisingly emerges as key to fostering genuine possibilities for dialogue among apparently antagonistic theological approaches.